Transcriptome Profiling Insights the Feature of Sex Reversal Induced by High Temperature in Tongue Sole Cynoglossus semilaevis - Liu, Jinxiang; Liu, Xiaobing; Jin, Chaofan; Du, Xinxin; He, Yan; Zhang, Quanqi (Frontiers in Genetics, 2019)
Abstract Sex reversal in response to temperature is common in fish and reptiles. Usually, the sex ratio shift occurs when embryogenesis experienced high temperature. Despite decades of work, the mechanism by which temperature during early development and sex reversal remains mysterious. In this study, we use tongue sole as a unique model to identify features from gonad transcriptome and epigenetic mechanisms related with cyp19a1a expression, in which temperature influences sex differentiation and female-specific marker has been detected. The sex ratio trended to males after high temperature treatment. RNA-seq data showed that the expression profiles of females and males were significantly different, and amount of genes were sexual dimorphic expression. The feature of pesudomales transcriptome was similar with males, but the genes involved in spermatogenesis and energy metabolism were differentially expressed. We speculated it was one of the reason that super females could not survive. Within the gonads, it was investigated that the methylation levels of cyp19a1a promoter were higher in females than in males and pseudomales. High-temperature treatment could increase the cyp19a1a promoter methylation levels of genotypic females. The results suggested that temperature induced masculinization involved DNA methylation, and mediated the regulation of cyp19a1a expression. A significant inverse relationship was observed between methylation levels and expression. In vitro, CpG within the cAMP response element (CRE) of the cyp19a1a promoter was hypermethylated, and DNA methylation decreased the basal and forskolin-induced activities of cyp19a1a promoter. Thus, these results suggested that epigenetic mechanisms involving DNA methylation might regulate the expression of cyp19a1a. It may be a mechanism widely used to drive sex reversal in teleost.